Effect of Local Feed Ingredients on Growth Rate of Sakini Chickens in Banke District, Nepal - Kafle, Ashok; Bhatt, Bhuwan Raj Bhatt; Nyaupane, Shankar; Neupane, Krishna Kanta; Dhital, Bhargab; Karn, Bimal Kumar Lal (Journal of the Institute of Agriculture and Animal Science, 2024)
The experiment was conducted in Poultry Development Farm, Khajura, Banke, Nepal from 23rd November 2020 to 1st March 2021 to study the growth performance of indigenous (Sakini) chicken fed with varied combinations of local ingredients such as Maize (M), Broken rice (BR) and Wheat (W) in diets. The treatments used were, commercial feed formulation (T1), 75% M (T2), 50% M + 25% BR (T3), 50% M + 25% W (T4) and 25% M + 25% BR + 25% W (T5). A completely randomized design (CRD) having five treatments with three replications and 14 weeks experiment from 6th week to 20th week were used for the study. In this experiment Benefit-Cost ratio of T5 is significantly higher (1.93±0.04) and T1 obtained lowest ratio (1.41±0.03); per unit cost of meat was significantly higher (NRs. 572.10±71.14) in T1 while lowest in T4 (NRs. 409.96±8.36); final body weight was recorded to be higher in T5 (1.74±0.04 kg) while lowest in T4 (1.59±0.13 kg); mean weight gain was higher in T5 (1.41±0.01 kg) and the lowest in T2 (1.30±0.02 kg); lowest FCR was obtained by T5 (4.17±0.15) and T1 (Control) obtained highest (4.61±0.11); weekly weight gain was observed highest in T5 (0.101±0.008 kg) while lowest in T2 and T4 (0.093±0.008 kg). According to above result of this study the experimental treatment T5 gave better result in terms of body weight, weight gain, FCR and B/C ratio and treatment T4 gave better result in terms of dressing percentage and per unit cost of meat production. From this study it was concluded that, the locally available feed ingredients can be used to prepare feed for indigenous chicken (Sakini) without affecting the growth and production performance to reduce feed cost.